Directed Differentiation of Pluripotent Stem Cells into Kidney - Morizane, Ryuji (Biomark Insights, 2015)
Pluripotent stem cells (PSCs), including embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), represent an ideal substrate for regenerating kidney cells and tissue lost through injury and disease. Recent studies have demonstrated the ability to differentiate PSCs into populations of nephron progenitor cells that can organize into kidney epithelial structures in three-dimensional contexts. While these findings are highly encouraging, further studies need to be performed to improve the efficiency and specificity of kidney differentiation. The identification of specific markers of the differentiation process is critical to the development of protocols that effectively recapitulate nephrogenesis in vitro. In this review, we summarize the current studies describing the differentiation of ESCs and iPSCs into cells of the kidney lineage. We also present an analysis of the markers relevant to the stages of kidney development and differentiation and propose a new roadmap for the directed differentiation of PSCs into nephron progenitor cells of the metanephric mesenchyme.